First description of deep benthic habitats and communities of oceanic islands and seamounts of the Nazca Desventuradas Marine Park, Chile - Tapia-Guerra, Jan M. (Sci Rep, 2021)
Seamounts and oceanic islands of the Chilean Exclusive Economic Zone at the intersection of the Nazca and Salas y Gómez ridges lie within one of the least explored areas in the world. The sparse information available, mainly for seamounts outside Chilean jurisdiction and shallow-water fauna of the Desventuradas Islands, suggests that the area is a hotspot of endemism. This apparent uniqueness of the fauna motivated the creation of the large Nazca-Desventuradas Marine Park (NDMP, ~ 300,000 km(2)) around the small islands San Felix and San Ambrosio in 2015. We report for the first time a detailed description of benthic microhabitats (i.e., centimeter to meter scale), macrohabitats (i.e., meter to kilometer-scale) and associated megafauna within the NDMP. Descriptions were based on analysis of fauna collected by trawling and ROV video observations from ~ 50 to 370 m depth. Rocky, coarse sand and silty sediment bottom habitats were observed at island slopes. In contrast, rocky and coarse sandy bottom habitats with a predominance of rhodoliths, thanatocoenosis, and other biogenic components were observed at seamounts. Mobile fauna and predators dominated the oceanic islands and nearby seamounts, whereas seamounts farther from the islands were dominated by sessile and hemisessile fauna that were mainly suspension and deposit feeders. Based on the register of 118 taxonomic units, our results provide an expanded and updated baseline for the benthic biodiversity of NDMP habitats, which seemed pristine, without evidence of trawling or anthropogenic debris.